Blending the "e" for effective learning at Open University Malaysia (OUM) - Zoraini Wati Abas; Ansary Ahmed; Hairudin Harun (2004)
An increasing number of higher educational institutions have embraced e-learning. Many of these institutions have, however, realized that blending the “e” with traditional pedagogies is more effective than offering an entire environment based on e-learning. The right mix of technology and media can more effectively cater to the variety of learning styles and learning conditions. At Open University Malaysia (OUM), the blended pedagogical approach has been adopted for the delivery of all its academic programmes. The three main approaches are face-toface learning, online learning and self-managed learning. These approaches involve a variety of media such as printed modules, multimedia, collaborative online discussions, classroom tutorials, laboratory sessions, a digital collection of e-books and e-journals, and so on. Since opening its doors in August 2001, OUM today has about 25,000 students spread over 16 academic programmes. More than 1,600 part-time tutors provide regular face-to-face tutorials. There are 31 learning centres located throughout the country to cater to the student population. The paper will describe OUM’s blended pedagogies. It will also present some of the challenges the University faces as it tries to propagate a new learning culture among its tutors and learners particularly for online learning. (Author's abstract)